A Self Regulated Learning in Biology Education Students University of Riau: Self Regulated Learning Ability - Surtika; Wan Syafi’i; Firdaus LN (Pedagogi Hayati, 2021)
The 21st century learning, the fourth industrial revolution, curricullum 2013 and the movement of freedom to learn reqruired student to have an independent learning. Therefore it is considered important to have Self Regulated Learning in learning process. This research was conducted in July-September 2021 at Biology Education University of Riau. This research was a descriptive research and used a quantitative approach to analyze Self Regulated Learning in students. This research used a sample of 58 students were selected by stratified random sampling technique. Meanwhile the data collection is done by giving a questionnaire and interview which includes three aspect of Self Regulated Learning: foretought and planning, performance monitoring and reflection on performance. Descriptive analysis and imdependent sample t-tes was utilized in the data analysis of this research. The result of analysis showed that the students of PBUD is better the ability in two phases, foretought and planning and performance monitoring meanwhile the student of SBMPTN better the ability in the reflection on performance. Of all three phases the abilily in performance monitoring in student is still average.